Scaling Climate-Smart Agriculture technologies and innovations in West and Central Africa through regional spillover mechanisms: Experiences from CORAF and way forward - Segnon, Alcade C; Obossou, Esdras; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Scaling CSA climate-smart agriculture (CSA) technologies and innovations is essential to address climate change impacts in agriculture and food systems in West Africa. Through engagement with existing regional institutions such CORAF, AICCRA piloted innovative approaches to scaling up CSA technologies and innovations in West Africa, including innovation pitching, business-to-business (B2B), and regional workshops. CSA innovation pitches and B2B approaches have created awareness and resulted in a high level of interest in CSA technologies beyond AICCRA anchored countries. Engagement through regional institutions has led to the adoption of CSA institutional innovations in Central Africa. The regional Science-Policy dialogue platform, an institutional innovation for mainstreaming CSA into agricultural development plans and investments, is formalized in the Central African region based on the experience of West African Alliance for CSA and the national science-policy dialogue platforms in West Africa. Science policy dialogue platforms are potential channels through which regional organizations can express their demands for CSA technologies in the scaling-up process in different countries. There is a further need to monitor the extent to which the intention and interest in CSA technologies are translated into concrete actions at national and regional level, as many CSA technologies are increasingly reaching more countries.